The Effect of Acid Sanitizers on the Microbiome of Re-use Water - Feye, Kristina M.; Micchichi, Andrew C.; Rubinelli, Peter M.; Knueven, Carl J.; Thompson, Dale R.; Kogut, Michael H.; Ricke, Steven C. (Frontiers in Sustainable Food Systems, 2020)
The poultry industry is a major consumer of fresh water; therefore, in order to reduce their environmental footprint and burden, companies are in the beginning stages of evaluating water for re-use. Re-use water is classified as water from the poultry plant that has been collected, sanitized, and used again during poultry processing. One of the most commonly used sanitizers in processing water is peracetic acid (PAA). Inorganic sanitizers, such as sodium bisulfate (SBS), have documented antimicrobial and sanitation effects on a variety of surfaces. In this study, SBS and PAA were compared for their ability to sanitize re-use water collected from a local poultry plant. Fresh, commercial poultry processing plant reuse water was collected at the end of a processing shift and used within one hour of the collection. Microcosms were used and live microorganisms were collected and evaluated for aerobic plate counts, total Enterobacteriaceae, and Salmonella load. The microcosms contained either SBS (1%, 2% or 3%) or 200 ppm PAA throughout the course of the study. Water samples were collected at 0, 15, 30, and 60 minutes post-sanitation. The water was evaluated for total Enterobacteriaceae and microbial load using traditional plating methods and the total DNA was extracted and sequenced using the 16S rDNA Illumina MiSeq v3 Platform targeting the V4 region of the prokaryote rDNA molecule. All sanitation methods resulted in nearly undetectable XLD and APC counts by 60 m (P < 0.05), with 1% and 2% SBS having a slight rebounding of APC counts by 60 m. The sequences were analyzed using the QIIME2.2018.08 pipeline. Changes in alpha diversity and beta diversity were indicated across time and by treatment group, which may reflect the cumulative effects of the sanitation treatment (killing, delayed killing, and the emergence of resistant populations). Based on the ANCOM results, SBS groups had less Pseudmonas and more Bacteriodes while PAA groups had greater Actiobacter (Q < 0.05). The results of this study indicate that SBS is as efficacious as PAA for decreasing bacterial loads in poultry reuse water, but it may favor different populations of bacteria in that water.